(3GdOQI GdfLajIs - (3GdOQGRj GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J (B1168s
(3ChdgG (B:s
(3HSe Gddg (B.. (3Qhi GdUOhb YWQ Gddg eQbOg aj cJGH Yjhf CNHGQ GdQVi Ydjg GdSdGe haj cJGH GdeLGdS HSfOg Yf GdMSf Hf Ydj Hf aVGd Yf GdQVi Ydjg GdSdGe Cfg bGd dg QLd ef Cgd NQGSGf (B...s
(3BNQgG (B:s
.. (3abGd eTQc hGddg Cj hGddg eTQc jdRe GdEQGH HGdLgd hgh eSJHYO ZjQge ef GdaQb GdePchQI dYOe Gdbhd hGdeLhS aGdCcKQ Ydi chfge efge dbhdg (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\215s
(3GdPQjYI (B8\529s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis